ENGLISH NATIONAL EXAMINATION FOR HIGH SCHOOL STUDENTS IN INDONESIA - Rahayuningtyas Agus Wahyuni (Soegijapranata Catholic University, 2006)
The importance of mastering English for Indonesian students is getting higher due to the globalization in all sectors. One measure to improve the mastery of English done by the government is by implementing the English National Examination with a passing grade of 4.25. There are two kinds of English National Examinations in the school year 2004/2005 and 2005/2006. One is based on the 1994 Curriculum and the other is based on the 2004 Curriculum. The English National Examination in Indonesia has included listening section since the school year 2003/2004. Ever since the application of the examination in the school year 2004/2005 there are many controversies about the National Examination with the passing grade of 4.25 nationally, but the government still goes on with the National Examination because it believes that the advantages outweigh the disadvantageous. The controversies, however, will decrease if the government does not use it to determine a students graduation.